Incidence and risk factors of falls in older adults after discharge: A prospective study - Siyu Long; Liangzhu Hu; Yetao Luo; Yaling Li; Fu Ding (Elsevier, 2023)
Objectives: This study aimed to determine the incidence of falls and risk factors associated with falling in discharged older adults. Methods: A prospective study was conducted on older adults who had been issued a discharge order in a Class A tertiary hospital in Chongqing, China, from May 2019 to August 2020. The risk of falling, depression, frailty, and daily activities were evaluated at discharge using the mandarin version of the fall risk self-assessment scale, Patient Health Questionnaire-9 (PHQ-9), FRAIL scale, and Barthel Index, respectively. The cumulative incidence function estimated the cumulative incidence of falls in older adults after discharge. And the risk factors of falls were explored using the sub-distribution hazard function in the competing risk model. Results: In a total of 1,077 participants, the total cumulative incidence of falls at 1, 6 and 12 months after discharge was 4.45%, 9.03%, and 10.80%, respectively. The cumulative incidence of falls in older adults with depression (26.19%, 49.93%, and 58.53%, respectively) and those with physical frailty (21.59%, 41.67%, and 48.73%, respectively) was much higher than that in those without depression and physical frailty (P < 0.05). Depression, physical frailty, Barthel Index, length of hospital stay, re-hospitalization, being cared for by others, and the self-assessed risk of falling were directly associated with falls. Conclusions: The incidence of falls among older adults discharged from the hospital has a cumulative effect with the lengthening of the discharge time. It is affected by several factors, especially depression and frailty. We should develop targeted intervention strategies to reduce falls for this group.